EKSISTENSI TARI JEPIN TALI BUI DESA KARIMUNTING KECAMATAN SUNGAI RAYA KEPULAUAN KABUPATEN BENGKAYANG - Monalisa Monalisa; Ismunandar Ismunandar; Winda Istiandini (Universitas Tanjungpura, 2020)
AbstractThis study aims to find out the clarity of the existence of Jepin Tali Bui Dance in Karimunting Village of Sungai Raya Kepulauan District of Bengkayang Regency. This study was conducted in the form of qualitative research with the descriptive method, using an ethnographic approach. The data were collected using observation, interviews, and documentary study techniques. The subjects of the study were the artists from the Joint Rukun Art Studio. The researcher acted directly as a research instrument. The data were validated using extended observation techniques, as well as source triangulation techniques that combine statements from the source. Based on the findings, Jepin Tali Bui existed since 1977, which was first inherited by Mr. Nalen, a native of the Malay tribe. This dance was popularized and developed in 2003, led by Ms. Suraddmi, son of Mr. Nalen, at the Art Studio Rukun Bersama. Since its existence, Jepin Tali Bui is used as entertainment. The result of this study can be contributed as a learning material in Culture and Arts subject for the eighth-grade class of Junior Highschool in Semester 1. Keywords: existence, Jepin Tali Bui dance.